Thomas Aquinas and social virtues of piety and respect: an outlook of the history of education - doi: 10.4025/actascieduc.v35i1.18906 - Oliveira, Terezinha (Acta Scientiarum. Education, 2012)
This study will analyze the relationship between education and politics at the University of Paris in the thirteenth century. The source for this study is based on two questions of the Summa Theologiae (II - II), written by Thomas Aquinas. They relate to the Question 101 on the Mercy, and Question 102, on Respect. When dealing with piety and respect, Master Thomas teaches his students the importance of tolerance and respect among men, so that life could elapse in the collective space. Given this urban environment, Thomas showed that the life in the city and in the university became complex, requiring people to have new concepts about social interaction, especially in relation to the ruler. Men, therefore, needed to learn the art of living together and the art of politics to meet new social laws. Reflecting on the writings of Master Thomas, we learn, through historical memory, how the theorists of earlier times were able to combine, in their writings and teachings, the knowledge to be taught as well as the guiding principles of politics as important for social relationship, regardless of historical time.